Structure, Evolution, and Functions of Bacterial Type III Toxin-Antitoxin Systems - Nathalie Goeders; Ray Chai; Bihe Chen; Andrew Day; George P. C. Salmond (Toxins, 2016)
Toxin-antitoxin (TA) systems are small genetic modules that encode a toxin (that targets an essential cellular process) and an antitoxin that neutralises or suppresses the deleterious effect of the toxin. Based on the molecular nature of the toxin and antitoxin components, TA systems are categorised into different types. Type III TA systems, the focus of this review, are composed of a toxic endoribonuclease neutralised by a non-coding RNA antitoxin in a pseudoknotted configuration. Bioinformatic analysis shows that the Type III systems can be classified into subtypes. These TA systems were originally discovered through a phage resistance phenotype arising due to a process akin to an altruistic suicide; the phenomenon of abortive infection. Some Type III TA systems are bifunctional and can stabilise plasmids during vegetative growth and sporulation. Features particular to Type III systems are explored here, emphasising some of the characteristics of the RNA antitoxin and how these may affect the co-evolutionary relationship between toxins and cognate antitoxins in their quaternary structures. Finally, an updated analysis of the distribution and diversity of these systems are presented and discussed.